2019
DOI: 10.1002/14651858.cd012128.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical interventions for symptomatic mild to moderate knee osteoarthritis

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 127 publications
(13 reference statements)
0
19
0
4
Order By: Relevance
“…Only seven SRs (4.2%) had high methodological quality, 23 29 of which all were Cochrane reviews. Eight (4.8%) had moderate quality, 25 (15.0%) had low quality, while the remaining 127 (76.0%) had critically low quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only seven SRs (4.2%) had high methodological quality, 23 29 of which all were Cochrane reviews. Eight (4.8%) had moderate quality, 25 (15.0%) had low quality, while the remaining 127 (76.0%) had critically low quality.…”
Section: Resultsmentioning
confidence: 99%
“…Overall methodological quality and associated factors. Only seven SRs (4.2%) had high methodological quality, [23][24][25][26][27][28][29] Final meta-analyses were included in this study (N=167) Results from multi-ordinal logistic regression analyses indicated that the following factors were associated with higher overall methodological quality ( Binary logistic regression analyses showed that SRs published in journals with a higher JIF had better performance in presenting the research question with PICO components (AOR 2.4, 95% CI 1.1-5.5) and considering risk of bias during meta-analysis (AOR 1.4, 95% CI 1.1-1.8). SRs published more recently were more likely to account for risk of bias when interpreting results (AOR 1.3, 95% CI 1.1-1.5).…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Indeed, a recently published systematic review that investigated the role of arthroscopic partial meniscectomy in knees with degenerative changes by extracting data from five randomized clinical trials (RCTs) found that patients with symptomatic meniscal tears and degenerative changes in the knee can benefit from arthroscopic meniscectomy, particularly if the osteoarthritis is mild 38 . However, other studies have suggested that the progression of OA may be more rapid in patients who underwent arthroscopic meniscectomy than in those who underwent conservative therapy 39,40 . There is still controversy regarding the influence of meniscectomy on the progression of OA 41,42 …”
Section: Discussionmentioning
confidence: 99%
“…38 However, other studies have suggested that the progression of OA may be more rapid in patients who underwent arthroscopic meniscectomy than in those who underwent conservative therapy. 39,40 There is still controversy regarding the influence of meniscectomy on the progression of OA. 41,42 There are limitations of this study that should be considered.…”
Section: Histopathological Changes In the Medial Meniscusmentioning
confidence: 99%
“…Cortisol, OA pain and surgery Surgery aims to remove the potential pain-generating mechanism (mechanical OA degradation) in OA, but many patients have a poor treatment response after surgery 42 . Cortisol levels rise with the physiological stress of surgery and the range in baseline levels and peak cortisol responses to surgery is wide 43 .…”
Section: Cortisol Oa Pain and Ethnicitymentioning
confidence: 99%